HUBUNGAN DIAMETER APENDIKS BERDASARKAN USG DENGAN SKOR ALVARADO PADA APENDISITIS AKUT - Fikra Safa Advancya Iman; Agung Ary Wibowo; Ida Yuliana; Winardi Budiwanata; Mashuri Mashuri (Homeostasis, 2022)
Appendicitis is the most common cause of acute abdomen and the most common surgical emergency. Signs and symptoms that are not always clear in every patient make it difficult to establish a diagnosis. This study aims to determine the relationship of the Alvarado score with the size of the diameter of the appendix based on ultrasound which can help in diagnosing cases of appendicitis. This research is an analytic observational study with a retrospective cohort study approach with a total sample of 52 people who have complied with the specified criteria and were selected by non-probability sampling technique. The data used for this study were the Alvarado score and the size of the diameter of the appendix based on the patient's ultrasound taken from secondary data. The Pearson correlation test conducted has shown a negative relationship between the Alvarado score and the size of the appendix diameter based on ultrasound with a p-value is 0,078>0.05. Based on this study, it can be concluded that there is no corellation between the size of the appendix diameter based on ultrasound and the Alvarado score in appendicitis patients of RSUD Ulin Banjarmasin